2012
DOI: 10.1073/pnas.1205838109
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of metabotropic glutamate receptor dimerization in agonist activation and G-protein coupling

Abstract: The eight metabotropic glutamate receptors (mGluRs) are key modulators of synaptic transmission and are considered promising targets for the treatment of various brain disorders. Whereas glutamate acts at a large extracellular domain, allosteric modulators have been identified that bind to the seven transmembrane domain (7TM) of these dimeric G-protein-coupled receptors (GPCRs). We show here that the dimeric organization of mGluRs is required for the modulation of active and inactive states of the 7TM by agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
133
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(150 citation statements)
references
References 54 publications
7
133
1
2
Order By: Relevance
“…In view of the fact that G-protein coupled receptor dimerization occurs soon after biosynthesis [20], it is also likely that these captive mGluR5 are in the dimer form. A growing body of evidence suggests that mGluR5 proteins are only functional in the form of disulfide-linked dimers [5,29], suggesting an increase in mGluR5 dimers represents an increase in functional mGluR5 units in the present study. However, considering reduced mGluR5 signaling (by mGluR5 knockout or pharmacological antagonism) produces schizophrenia-like behaviors, and mGluR5 PAMs have therapeutic efficacy in preclinical rodent models [see 18], we hypothesize a model of mGluR5 dysregulation in which higher protein expression and dimer units does not represent increased activity and/or function in the schizophrenia brain, but rather, alterations to mGluR5 localization (Fig 4a and b) and also signaling (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…In view of the fact that G-protein coupled receptor dimerization occurs soon after biosynthesis [20], it is also likely that these captive mGluR5 are in the dimer form. A growing body of evidence suggests that mGluR5 proteins are only functional in the form of disulfide-linked dimers [5,29], suggesting an increase in mGluR5 dimers represents an increase in functional mGluR5 units in the present study. However, considering reduced mGluR5 signaling (by mGluR5 knockout or pharmacological antagonism) produces schizophrenia-like behaviors, and mGluR5 PAMs have therapeutic efficacy in preclinical rodent models [see 18], we hypothesize a model of mGluR5 dysregulation in which higher protein expression and dimer units does not represent increased activity and/or function in the schizophrenia brain, but rather, alterations to mGluR5 localization (Fig 4a and b) and also signaling (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, the glutamate affinity on the isolated ECDs is very similar to that determined on the full-length receptor 51,[55][56][57] . Moreover, we showed that on a an isolated 7TM domain of mGlu2R and on a full-length monomeric mGlu2R construct reconstituted in lipids nanodiscs, positive and negative allosteric modulators acted as full agonists and antagonists, whereas glutamate alone had no effect 9 . The activation of the G-protein by glutamate was recovered upon using of the full-length dimeric receptor, underlying the key role of the ECDs, as a dimer, in the activation process 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we showed that on a an isolated 7TM domain of mGlu2R and on a full-length monomeric mGlu2R construct reconstituted in lipids nanodiscs, positive and negative allosteric modulators acted as full agonists and antagonists, whereas glutamate alone had no effect 9 . The activation of the G-protein by glutamate was recovered upon using of the full-length dimeric receptor, underlying the key role of the ECDs, as a dimer, in the activation process 9 . In summary, we clearly demonstrate that the extracellular domain of the mGluR exists in a preformed equilibrium of conformational states and that the exclusive role of ligands is to modulate the transition rate between states, rather than stabilizing individual conformations at the expense of others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations